Sustainable Development Strategies For Sasak Beach To Enhance Tourist Visits - Rika Andriani; Yulhaslinda (CV Putra Publisher, 2026)
The Sasak Beach tourist attraction in West Pasaman Regency has significant natural tourism potential to support regional economic growth. However, its management still faces various obstacles, such as limited facilities, low community participation, suboptimal digital promotion, and the underdevelopment of a tourism-based creative economy. This study aims to analyze the current development strategy for the Sasak Beach tourist attraction and identify factors that can be developed to increase tourist visits. The study used a qualitative approach with a descriptive research type. Data were obtained through observation, in-depth interviews, and documentation with informants consisting of the Tourism Office, village government, tourist attraction managers, Tourism Awareness Groups (Pokdarwis), MSMEs, the community, and tourists. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data condensation, data presentation, and drawing conclusions. The results show that the Sasak Beach development strategy has been directed at improving infrastructure, preserving the environment, strengthening tourist attractions, and collaboration between the government and the community. However, improvements in human resource quality, strengthening digital-based promotion, providing unique souvenirs, developing MSMEs, improving visitor comfort, and partnerships with the private sector are still needed. This study concludes that the development of Sasak Beach requires an integrated and sustainable strategy to be able to increase the competitiveness of the destination while increasing the number of tourist visits and the welfare of the local community.